Pengaruh Strategi Pemasaran, Saluran Distribusi Dan Promosi Terhadap Keputusan Pembelian Keripik Singkong Permata (Studi Kasus Umkm Keripik Singkong Permata Kecamatan Pakis Kabupaten Malang) - Bi’rul Ulumia; Muhammad Mansur; M Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to determine the relationship between the variables of marketing channels, distribution channels, and promotions on purchasing decisions. The location of the research is in UMKM Keripik Singkong Permata, Pakis District, Malang Regency. This research is a quantitative research. Data collection techniques using a questionnaire. The data analysis technique used in this research is using multiple linear regression analysis. Based on the results of data analysis that the variables of marketing strategy, distribution channels, and promotions have a positive simultaneous effect on consumer purchasing decisions at UMKM Keripik Singkong Permata. Partially, marketing strategies have a positive effect on purchasing decisions that are oriented to the formation of product innovation, service innovation, place innovation, promotional innovation used by UMKM’s managers/owners. Partially, distribution channel variables also positively influence purchasing decisions, with the orientation of the formation of product availability, ease of obtaining products, and fast food. Partially, the promotion variable has a positive effect on consumer purchasing decisions, with the orientation of introducing products, techniques to attract consumers, offering product advantages, promotional content carried out by UMKM Keripik Singkong Permata in Pakis District, Malang Regency.Keyword: Marketing Channels, Disributions Channels, Promotion, Purchasing Decisions